PENGARUH ADVERSITY QUOTIENT, EMOTIONAL QUOTIENT, DAN STRES TERHADAP PRESTASI AKADEMIK MAHASISWA ( STUDI KASUS PADA MAHASISWA YANG MENGIKUTI ORGANISASI MAHASISWA DI UNIVERSITAS AHMAD DAHLAN) - Ahmad Sudirman; Ani Muttaqiyathun (Jurnal Fokus Manajemen Bisnis, 2018)
This research main goals is to know the influence of an adversity quotient, emotional quotient and stress towards academic achievement among student who join organisations in Universitas Ahmad Dahlan. This research was a survey research using questionnaire as an instrument. Population of this research was a student who join organisation in Universitas Ahmad Dahlan. The sample that used was student who join an organisation such as DPM, BEM, HMPS and UKM from 2017 to 2018 school years that consist of 289 respondent with a proposional rundwon sampling technic. Instrument validation test was used pearson product moment, while the reliability was used alpha cronbach. Analysis technic that used was a mutiple reggresion analysis technic. The result of this research showing that adversity quotient variable (X1) has significant effect to academic achievement. emotional quotient variable (X2) has no significant effect to academic achievement. stress variable (X3) has significant effect to academic achievement. adversity quotient, emotional quotient and stress at the same time has a significant effect to academic achievement.